Lionel J. Skidmore training manuals - Skidmore, Lionel J.
Ballistic Missiles, Revision I (volumes I-IV; March 1960) used by Skidmore for the Air Force Ballistic Missile Division, Space Technology Laboratories, inc.
Scientist.
Collection material in English.
Keywords: Space Technology Laboratories, inc; Ballistic missile defenses; Ballistic missiles; Military weapons; Scientists